Toward a study of Λ(1405) via the d(K-, πΣ) reaction - Omar, Zh. (Хабаршы. Физика сериясы, 2018)
There is a long-standing argument if Λ(1405) is a KbarN bound system. Theoretical analyses of Chiral Unitary model, suggests a double-pole structure of Λ(1405): Σπ and KbarN. The theoretical statement about the double pole structure of Λ(1405) shows a new picture of Λ(1405) as a resonant meson-baryon state, which is different from the so-called traditional picture of Λ(1405). In order to solve above-mentioned questions, it is necessary to clarify how Λ(1405) is coupled to KbarN. Therefore, we have conducted an experiment to study Λ(1405) in KbarN scattering (E31). Since Λ (1405) cannot be formed directly from the K-p reaction in free space, we use the d(K-, n)Σπ reactions at a kaon momentum of 1GeV / c, where we expect the incident kaon to knock out a neutron in the deuteron and the recoiled Kbar reacts with the residual nucleon with the formation of Λ(1405). We have finished a beam time for the second run of E31 in January and February, 2018. The E31 experiment is performed at the K1.8BR beam line in the Hadron Experiment Hall of J-PARC. In the second run, by increasing statistics to several times, we expect to measure Λ(1405) in the Σ+π-/Σ-π+ invariant mass spectra in the d(K−, Σπ)”n”. In particular, we expect to measure angular dependence of widely production of Λ(1405) in the d(K−, Σπ ) reaction.